The Effect of Subjective Perception of Work in Relation to Occupational and Demographic Factors on the Mental Health of Polish Nurses - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Sobolewski, Marek (Frontiers in Psychiatry, 2020)
Introduction: Nursing is considered one of the most stressful professions in the world. The high emotional burden associated with excessive workload in qualitative and quantitative terms, exposure to existing and emerging infectious diseases, daily confrontation with the suffering of individuals and their families and low social support leads to the development of numerous stress reactions among nurses, resulting in the development of anxiety, insomnia, social dysfunction and depression. Indeed, somatic and mental stress-related disease rates are higher among nurses than in the general population. Aim: To determine the impact of subjective work characteristics on the mental health of nurses in relation to demographic and occupational factors. Material and method: The research was carried out among 558 nurses working in hospitals in Podlaskie Voivodeship, and used the Subjective Work Evaluation Questionnaire (SWEQ) by Dudek et al. and Goldberg’s GHQ-28 Questionnaire. Results: As measured by SWEQ, and as self-assessed by means of the GHQ-28 questionnaire, overall stress negatively affects the nurses' health (R2=18.7%). Among the partial measures of the SWEQ questionnaire, work overload had strong and the lack of rewards, social relations and lack of support had weak negative effect on the overall mental health assessment of nurses (R2=19.2%). The Responsibility measure was an exception that had a positive impact on the nurses' well-being. Among occupational and demographic factors, only higher education in relation to secondary education in interactions with the overall stress measure and unpleasant work conditions had a positive effect on the overall mental health self-assessment of nurses (R2= 20.7%). Conclusions: The results of our study provide a clear message to the hospital management that improving the work organization and atmosphere of nurses by reducing perceived work overload and increasing the responsibility of nurses can have a positive impact on their mental health. Encouraging nurses to improve their education can result not only in an obvious improvement in staff qualifications, but also in better resistance to stressors in the workplace and, consequently, in better staff well-being. Both measures can have a positive impact on the quality of care provided by nurses and on reducing staff turnover.